The Authority of the Teacher – as the Necessary Condition for Effective Interaction with Students - Machynska, Nataliia (Pedagogical Discourse, 2015)
The article is emphasized on the authority of the teacher, which determines the qualitative characteristics of the individual teacher professionalism. By relying on the results of the theoretical and practical research, the author defines the role and place of the teacher, his or her authority in the organization of effective pedagogical interaction at different levels of communication. Describing the individual components of the authority of the teacher, particular attention is paid to the general and professional culture of the teacher and singled out the negative signs of manifestation. It is indicated that basis of the authority of the teacher is his professional competence, covering the structure in tact teaching, teaching techniques, teaching ethics. It was found out that the authority of the teacher is based on the pedagogical communication that affects the development and shaping both the individual teacher and the individual student. Based on the results of the experimental studies, the author defines the features of formation of pedagogical authority in the lectures, and points to the objective difficulties of the uphold of the authority of the teacher, offers some advices on the formation of authority in the system of pedagogical interaction at the following levels: «teacher-student», «teacher-administration», «student-student»,